Rhodoscirpus (Cyperaceae: Scirpeae), a new South American sedge genus supported by molecular, morphological, anatomical and embryological data - Léveillé Bourret, Étienne (2015)
In its broadest sense, Scirpus consists of a heterogeneous assemblage of up to 250 species, but modern circumscriptions suggest that only 40–50 species are part of the genus. Despite a narrower definition of the genus, atypical species continue to be segregated from Scirpus with a common pattern being the removal of Southern Hemisphere taxa to other genera and tribes. In South America, the morphology of remaining Scirpus species also suggests that they are not closely related to Scirpus s.str., but most of these taxa are only known from their types, making a detailed analysis of their generic affinities difficult. One notable exception is Scirpus asper, a species that is relatively common in the mountains and adjacent lowlands of Peru south to Argentina. Although this species possesses features used in the circumscription of Scirpus, such as cauline leaves, flat leaf blades and anthelate inflorescences, it is known to differ from Scirpus s.str. by its Schoenus-type embryo, and most of its presumed allies are now placed in different genera (e.g., Scirpus analecti ≡ Cypringlea analecta; Scirpus giganteus ≡ Androtrichum giganteum). In this study, we use DNA sequence data from the plastid (matK, ndhF) and nuclear (ETS-1f) genomes to demonstrate that Scirpus asper is not closely related to Scirpus s.str., but sister to Phylloscirpus within the predominantly South American Zameioscirpus clade (Amphiscirpus, Phylloscirpus, Zameioscirpus). When combined with morphological, anatomical and embryological data, results indicate that S. asper is best treated as the sole species of a new monotypic genus, Rhodoscirpus. The implications of these results on the taxonomy of tribe Scirpeae are discussed.